Challenges and Strategies of Teachers in Integrating Canva in English Classroom Teaching - Syahdan Syahdan; Herlinawati Herlinawati; Syaifullah Syaifullah; Dinda Triana Syafitri (ELT-Lectura, 2023)
Information Communication Technology (ICT) has been applied and integrated into education that enhances teachers to explore various teaching and learning strategies, materials, and media. This study aims to discover the experiences of English teachers in the use of Canva, an ICT application, to create an attractive presentation of teaching English. The researchers employed Generic Qualitative Research to investigate the challenges and strategies in using the application. The researchers interviewed two English teachers responsible for teaching English at the high school, junior high school, and elementary school levels at the SMART Indonesia Pekanbaru. The instruments used in this research were interviews and documentation. To analyze the data, the researchers transcribed the interview and employed thematic analysis by identifying patterns or finding themes in the interview data. The researchers found two challenges the teachers faced in the research findings: low internet connectivity and the limitation of templates availed in the free version Canva application. In the meantime, to cope with the challenges, the teachers used two strategies, providing learning modules and adding pictures for an attractive appearance. In advance, the researchers found that the teachers benefitted from Canva's application in English classroom teaching. In conclusion, though English teachers experience challenges with the Canva application, they can anticipate them and benefit from using the learning application for teaching English.